Shall I call, text, post it online or just tell it face-to-face? How and why Flemish adolescents choose to share their emotions on- or offline. Issue 1 (2nd January 2018) - Vermeulen, Anne; Vandebosch, Heidi; Heirman, Wannes
Abstract: Social sharing of emotions is a frequently used emotion regulation strategy. This study adds to the emotion regulation literature and the affordances of technologies perspective by providing a better understanding of with whom adolescents share emotions on- and offline, how they do this and why they use certain modes. In-depth interviews with 22 Flemish adolescents (aged 14–18) show that these youngsters share almost all experienced emotions, often with multiple recipients and using multiple communication modes. Although they mostly prefer sharing emotions face-to-face, they also share by texting, calling, or posting something on Twitter, Facebook, Snapchat, or Instagram. Our respondents generally make a more or less conscious decision about what and how to share. The valence, type, and intensity of the emotion, the affordances of the mode, social norms, and impression management concerns influence this decision.